The Relationship Between Cote D'ivoire's Political Situation And Burkina Faso's Maritime Transit Cargo Throughput That Passed Through Ghana (International Journal of Technology and Management Research, 2020)
Ghana rose from an insignificant position in 1997/8 to become the topmost maritime transit corridor for landlocked countries in West Africa and particularly for Burkina Faso around 2006. Since then, Ghana's transit corridor has, generally, been recording a declining trend in the yearly percentage throughput of Burkina Faso's maritime transit cargo that is transported along it. Popular opinion in the transit business in West Africa suggests a negative relationship between the level of Ce d'Ivoire's political stability and Burkina Faso's maritime transit cargo throughput that is transported along Ghana's transit corridor. This work, using data drawn from 1998, 2000 and 2002-2014 investigated the empirical veracity of such an opinion. Data were sourced from World Governance Indicators and also through questionnaires that were administered to a sample drawn from five major stakeholder official institutions involved in transit trade in Ghana. The study found a significant negative relationship between Ce d'Ivoire's political stability rank and Burkina Faso's maritime transit cargo throughput that was transported through Ghana's corridor over the specified period. The study, among others, recommends a reduction in the number of transit check points and the associated delays and bribery along Ghana's road corridor so as to make it more efficient and competitive in West Africa. Keywords: Land-locked country; transit; cargo; throughput; corridor; and 'transitor'